2017
DOI: 10.22190/teme1702475v
|View full text |Cite
|
Sign up to set email alerts
|

Веза Између Традиционалне Хране И Лојалности Туриста Према Руралним Дестинацијама

Abstract: Gastronomy tourism can be regarded as a travel to a destination for cultural purposes with experiences of unique and traditional foods at the destination. Based on this, the main hypothesis is set. It follows that traditional food is one of the main reasons for loyalty of tourists. The paper is based on empirical research carried out amongst 328 foreign tourists from eight countries who visited six traditional farm houses (Salaši) in rural destination of Vojvodina (Serbia) in August 2015. The purpose of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Rural tourism has the potential for significant development in the future, as attractive elements are diverse and their combination and complementarity can provide a very wide range of tourism products (a product intended for hikers, excursionists, nature lovers, pupils, etc.). Traditional food could also be a strong reason for the loyalty of tourists to rural areas [68]. A special element in attracting tourists is the kindness of the hosts, their preserved traditional way of life, and their hospitality towards the guests of the village.…”
Section: Discussionmentioning
confidence: 99%
“…Rural tourism has the potential for significant development in the future, as attractive elements are diverse and their combination and complementarity can provide a very wide range of tourism products (a product intended for hikers, excursionists, nature lovers, pupils, etc.). Traditional food could also be a strong reason for the loyalty of tourists to rural areas [68]. A special element in attracting tourists is the kindness of the hosts, their preserved traditional way of life, and their hospitality towards the guests of the village.…”
Section: Discussionmentioning
confidence: 99%
“…Alibabić et al (2012) found in a study of the Bosnian cuisine that poor style of presentation of the Bosnian cuisine was noticed in many restaurants. This could influence the perception of tourists about the heritage presentation of a dish (Vujko et al, 2017). It shows the importance of the right style of presentation of certain heritage dishes to be known by the consumers.…”
Section: [B]mentioning
confidence: 99%
“…The challenge of adjusting authentic recipes to satisfy tourist demands may lead to authenticity risks (Almansouri et al, 2022;Chhabra, 2005;Lu & Fine, 1995). For instance, in a study of the Bosnian cuisine, (Alibabić et al, 2012) found there was a poor style of presentation in many restaurants serving tourists (Vujko et al, 2017). Food safety risks may also differ because of the different characteristics of FSEs (Luning et al, 2013).…”
Section: Introductionmentioning
confidence: 99%